2020
DOI: 10.1039/d0qi00901f
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the labile site in dinuclear [Pd2L2]n+ metallo-cycles: multi-step control over binding affinity without alteration of core host structure

Abstract: While Nature often controls supramolecular processes through regulation giving multiple levels of activity, synthetic metallosupramolecular systems have generally been binary (e.g. on/off) when they have control over molecular recognition events,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“… 16 The addition of halide anions to positively charged hosts can trigger the uptake of neutral guest molecules. 17 Guest uptake can also be tuned in redox-responsive systems. 18 Sophisticated pH effects have recently been investigated 19 and combined with light, leading to reversible cage disassembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 The addition of halide anions to positively charged hosts can trigger the uptake of neutral guest molecules. 17 Guest uptake can also be tuned in redox-responsive systems. 18 Sophisticated pH effects have recently been investigated 19 and combined with light, leading to reversible cage disassembly.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that interaction of such cages with chemical stimuli, e.g., additional ligands, allows structural rearrangement and guest release . The addition of halide anions to positively charged hosts can trigger the uptake of neutral guest molecules . Guest uptake can also be tuned in redox-responsive systems .…”
Section: Introductionmentioning
confidence: 99%
“…Related work in our group with a similar 2 + 2 dimer has since shown that the solvent molecule can be exchanged for halide ions, influencing the electronic character of the dimer and hence its capacity to interact with a neutral electron rich platinate guest. 86…”
Section: Discussionmentioning
confidence: 99%
“…Related work in our group with a similar 2 + 2 dimer has since shown that the solvent molecule can be exchanged for halide ions, influencing the electronic character of the dimer and hence its capacity to interact with a neutral electron rich platinate guest. 86 With 2 AD -pyridine at a 4 : 3 ratio between ligand and metal ion, the stoichiometry is sufficient for maximal binding site occupancy of the ligand. At low concentrations, both mononuclear [Pd(2 ADpyridine) 2 ] 2+ and dinuclear [Pd 2 (2 AD -pyridine) 2 (solvent) 2 ] 4+ were observed, together with a third species, which 1 H DOSY NMR spectroscopy revealed to have a larger hydrodynamic radius.…”
Section: Mixed Orthogonal Systemsmentioning
confidence: 99%
“…They are easily obtained in the reaction of cis-protected metal fragments, such as palladium­(II) [Pd­(II)] complexes, with appropriate N-heterocyclic compounds as ligands. Pd­(II) has been one of the most favored metal centers for self-assembly of metallacalixarenes because of its structural advantage of the square-planar coordination. Various Pd­(II) fragments are utilized to construct metal–organic structures with a range of topologies upon complexation with ligands. When a cis-protected Pd­(II) compound [Pd­(N^N)] (M) is treated with a suitable nonchelating or chelating bidentate ligand L, an M x L y -type self-assembled complex with the formula [Pd x (N^N) x ( L ) y ]­(monoanion) z could be obtained, with nitrate as the monoanion, hexafluorophosphate or perchlorate as counteranions, and “N^N” as the cis-protecting unit using a chelating bidentate compound with or without a π-cloud as the second ligand, including 2,2′-bipyridine (bpy), 1,10-phenanthroline (phen), 2,2′-dimethyl-bipyridine (dmbpy), ethylenediamine (en), and tetramethylethylenediamine (tmen). , Nitrogen donor compounds are most widely used as a nonchelating bidentate ligand L to construct complexes such as pyridine/pyrimidine in neutral formulas and imidazole/pyrazole in neutral or anionic formulas. …”
Section: Introductionmentioning
confidence: 99%